2011
DOI: 10.6026/97320630007393
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular identification of the metacestode parasitizing the liver of rodent hosts in bamboo growing areas of mizoram, northeast India

Abstract: In Mizoram (Northeast India), rodent outbreaks are known to occur periodically with the onset of bamboo flowering causing a tremendous destruction to food grains and as per the folk belief, often resulting in famine. In an exploratory survey of rodent pests in bamboo growing atreas for their helminth parasite spectrum, metacestodes of tapeworms were frequently encountered infecting the liver lobes and body cavity of the host. The morphological criteria were found to be closely consistent with the metacestode o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…The morphological characteristics of the present H. taeniaeformis specimens are consistent with previous work in Egypt [29] and in India [37], who detected and described metacestode infection in R. rattus. We detected pseudosegmentation along the strobila and a small terminal bladder, correlating with [9,38], who reported H. taeniaeformis to be the only metacestode in which the scolex is not invaginated at the bladder but rather attached to it through strobilae.…”
Section: Discussionsupporting
confidence: 92%
“…The morphological characteristics of the present H. taeniaeformis specimens are consistent with previous work in Egypt [29] and in India [37], who detected and described metacestode infection in R. rattus. We detected pseudosegmentation along the strobila and a small terminal bladder, correlating with [9,38], who reported H. taeniaeformis to be the only metacestode in which the scolex is not invaginated at the bladder but rather attached to it through strobilae.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, Theis and Schwab, 35 reported a 3.4% prevalence of T. taeniaeformis in Peromyscus maniculatus from California, and Wanas et al 19 found the parasite in Gerbillus gerbillus (33.3%), Acomys cahirinus (16.6%), and Arvicanthis niloticus (7.2%).Moreover, the presence of C. fasciolaris was established in R. rattus wild populations in bamboo forests from Mizoram, India. 20 None of the rodents captured from wild environments in this study were positive for C. fasciolaris infection. Absence of a wild transmission cycle that includes rodents may be due to the presence of five indigenous wild feline species that can act as final hosts: Herpailurus yagouaroundi, Leopardus pardalis, Leopardus wiedii, Puma concolor, and Panthera onca.…”
Section: Resultsmentioning
confidence: 68%
“…Metacestodes were stained with Semichon's acetic carmine, mounted on slides with Canada balsam medium and observed under a conventional stereoscope (OLYMPUS-SZ51, Tokyo, Japan). Characterization was performed according to morphological traits described by Bowman et al 33 and Malsawmtluangi et al 20…”
Section: Biological Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is recommended to practice depopulation of the infected colonies for the control of both parasites [ 3 ]. Both parasites had been reported from Mizoram [ 20 - 21 ].…”
Section: Introductionmentioning
confidence: 99%